Association between nutritional status and outcome of childhood acute lymphoblastic leukemia treated with Wijaya Kusuma Protocol - Fransiska Herintya; Sri Mulatsih; Endy Paryanto Prawirohartono (Paediatrica Indonesiana, 2008)
Background Acute lymphoblastic leukemia (ALL) is the mostcommon malignancy in childhood. Malnutrition in malignancypatients including ALL is one of major problems. This conditionis found at the time of diagnosis as a result of the disease itself orafter, chemotherapy or radiation. Many studies have beenconducted to determine the relationship between nutritional stateand outcome of childhood ALL patients but the result was stillcontroversial.Objective To determine relative risk of death and relapse inchildhood standard-risk ALL who received therapy using WijayaKusuma protocol.Methods This was a retrospective cohort study. Newly-diagnosedpatients since May 1999-December 2004 were taken for this study.Body mass index was used to measure nutritional status for >2years old children, and weight-for-height was used for those of=2 years old. Data was obtained from Yogyakarta Pediatric CancerRegistry Dr. Sardjito Hospital. Chi-squared test was used to analyzethe proportion difference and risk relative was used to determinerisk for death and relapse.Results One-hundred and forty five patients included in this study.There was no association between nutritional state and relapse(RR 1.1, 95% CI 0.76;1.61). Logistic regression analysis showedthat there was association between nutritional state and death(RR 2.34, 95% CI 1.01;5.45). Sepsis and relapse have contributionto death as well (RR 6.75, 95% CI 2.9;15.4 and RR 3.2, 95% CI1. 3;8.08 respectively).Conclusion Nutritional status is not associatiated with relapsebut is associated with death of ALL children.